PD-L1 Expression and Tumour Microenvironment Patterns in Resected Non-Small-Cell Lung Cancer - Gurevičienė, Giedrė; Matulionė, Jurgita; Poškienė, Lina; Miliauskas, Skaidrius; Žemaitis, Marius (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: Although perioperative immunotherapy is implemented as a standard of care for resected non-small cell lung cancer (NSCLC), there is unmet need for predictive biomarkers as programmed death-ligand 1 (PD-L1) is not the perfect one. The functionality of tumour-infiltrating immune cells in the tumour microenvironment (TME) and the involvement in immune system response is one of the crucial factors that lead to pro- or anti-tumourigenic role and could predict response to PD-1 and PD-L1 inhibitors. So, the investigation of PD-L1 expression in the context of TME in early stages of resected NSCLC is urgent required. Materials and Methods: PD-L1 expression by three scoring methods: tumour proportion score (TPS), immune cell score (IC), and combined proportion score (CPS) was assessed in 72 archival tumour tissue specimens from stage I–III surgically resected NSCLC patients and associations with immune cells in TME were explored. Results: PD-L1 expression ≥1% evaluated by TPS, IC, and CPS was detected in 28%, 36%, and 39% of cases and moderate, substantial, and strong agreement between TPS and IC, TPS and CPS, CPS and IC was detected (Cohen’s κ coefficient 0.556, 0.63, and 0.941, respectively). PD-L1 TPS, IC, and CPS correlated with smoking intensity defined as pack-years (r = 0.0305, p = 0.012; r = 0.305, p = 0.013, and r = 0.378, p = 0.002, respectively). Only PD-L1 TPS was associated with squamous cell carcinoma (p = 0.028). PD-L1 IC ≥1% was more often seen in tumours with high CD4+ T cells infiltration (p = 0.02), while PD-L1 CPS ≥1%—in tumours with high CD4+ and CD8+ T cells infiltration (p = 0.021 and p = 0.048, respectively). PD-L1 IC and CPS ≥10% was more often detected in tumours with greater number of tumour-infiltrating CD4+Foxp3+ T cells (p = 0.01 and p = 0.025, respectively). PD-L1 TPS ≥50% was associated with higher probability to detect greater number of tumour-infiltrating M2 macrophages (p = 0.021). No association was found between PD-L1 alone or in combination with tumour-infiltrating lymphocytes, macrophages, and disease-free or overall survival. Conclusions: This study results revealed that rates of PD-L1 expression correlated among three scoring methods (TPS, IC, and CPS). Moreover, PD-L1 expression was significantly associated with smoking intensity, squamous histology, and tumour-infiltrating immune cells.